Depth area duration analysis of short duration rainfalls (MAUSAM, 1995)
Depth Area Duration (DAD) analysis for the extreme rainfall events forms an important step in the hydrological design for the water resources structures. Review of literature reveals that enormous amount of work has been done concerning the DAD analysis for large duration (i.e. one day or more) storms. However, no work is reported so far on this aspect for storms having shorter duration. i.e. less than one day:Hourly rainfall data for 36 rainfall stations have been analysed  to develop simple DAD-relationship. This analysis pertains to the catchments of the rivers, namely Ramganga, Gomati, Yamuna  and Ghaghara.